Empowering MSMEs to Improve Family Economy - Dila Erlianti (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Empowerment of Micro, Small, and Medium Enterprises (MSMEs) is a crucial strategy for enhancing business capacity and family economic welfare. This community service activity employed a participatory approach and continuous mentoring to actively involve MSME actors in all stages, from planning, training, to evaluation. The results indicate an increase in MSME actors' understanding of proper business management, systematic financial recording, and effective marketing strategies. Additionally, technical skills improved, including the ability to maintain daily cash books, income-expenditure reports, and manage operational costs and business capital. The impact of this activity is reflected in increased income, family economic stability, and enhanced economic independence of MSME actors. These findings highlight that MSME empowerment through a participatory approach and sustained mentoring contributes to family economic improvement, community economic resilience, and inclusive, sustainable local economic development